Semiconductor Disk Lasers: Recent Advances in Generation of Yellow-Orange and Mid-IR Radiation. (20th December 2011) - Guina, Mircea; Härkönen, Antti; Korpijärvi, Ville-Markus; Leinonen, Tomi; Suomalainen, Soile
Abstract : We review the recent advances in the development of semiconductor disk lasers (SDLs) producing yellow-orange and mid-IR radiation. In particular, we focus on presenting the fabrication challenges and characteristics of high-power GaInNAs- and GaSb-based gain mirrors. These two material systems have recently sparked a new wave of interest in developing SDLs for high-impact applications in medicine, spectroscopy, or astronomy. The dilute nitride (GaInNAs) gain mirrors enable emission of more than 11 W of output power at a wavelength range of 1180–1200 nm and subsequent intracavity frequency doubling to generate yellow-orange radiation with power exceeding 7 W. The GaSb gain mirrors have been used to leverage the advantages offered by SDLs to the 2–3 μ m wavelength range. Most recently, GaSb-based SDLs incorporating semiconductor saturable absorber mirrors were used to generate optical pulses as short as 384 fs at 2 μ m, the shortest pulses obtained from a semiconductor laser at this wavelength range.